Analisis perbandingan rencana strategis pada perbankan syariah untuk meningkatkan kinerja - Cahyati, Ratih Nur; Ayu, Diyah Isti (Maliki Interdisciplinary Journal, 2023)
The strategic plan in banks is a process for realizing the vision and mission by formulate goals, targets and steps strategically. Strategic plans can determine what the bank will do, and how it will try or achieve its goals the. Each bank certainly has a different strategic plan. With Given this, this research aims to analyze the strategic plan of Bank NTB Syariah, Bank Bukopin Syariah, and Bank Victoria Syariah in 2022. With used descriptive qualitative research methods and secondary data for this research found that the strategic plans used by the three banks were different, However, all three banks have the same goal, namely to improve performance and make a positive contribution to economic growth.